Tyrosine-hydroxylase-containing vagal afferent neurons in the rat nodose ganglion are independent from neuropeptide-Y-containing populations and project to esophagus and stomach - Kummer, Wolfgang; Bachmann, Sebastian; Neuhuber, Winfried L.; Hänze, Jörg; Lang, Rudolf E. (Cell & tissue research, 1993)
Immunoreactivity to the rate limiting enzyme of catecholamine synthesis, tyrosine hydroxylase, has been described in the inferior sensory (= nodose) ganglion of the vagal nerve in the rat. The aim of the present study was to characterize further this neuronal population. The neurons do not represent displaced autonomic efferent neurons, since they do not receive synaptic input, as indicated by the absence of synaptophysin-immunoreactive terminals. In addition to the immunoreactivity to tyrosine hydroxylase, a tyrosine hydroxylase cRNA probe hybridizes with nodose ganglion neurons as demonstrated by in situ hybridization and Northern blotting. Many but not all of the tyrosine hydroxylase-immunoreactive neurons are also immunoreactive to the dopamine synthesizing enzyme, aromatic-l-amino-acid-decarboxylase, but lack the noradrenaline-synthesizing enzyme, dopamine-β-hydroxylase, thus favoring synthesis of dopamine. Neuropeptide Y, which is often colocalized with catecholamines, is also present in a subset of nodose ganglion neurons, as indicated by immunohistochemistry, in situ hybridization and Northern blotting. However, double-labeling immunofluorescence has revealed that these two antigens are localized in different cell populations. Retrograde neuronal tracing utilizing fluorescent dyes (Fast blue, Fluoro-gold) combined with tyrosine hydroxylase immunohistochemistry has demonstrated that the esophagus and stomach are peripheral targets of tyrosine-hydroxylase-containing vagal visceroafferent neurons.